Empireworld : How British Imperialism Shaped The Globe - Sanghera, Sathnam (UK: Viking, 2024)
"2.6 billion people inhabit former British colonies. The empire's influence upon the quarter-planet it occupied, and its gravitational influence upon the world outside it, has been profound from the spread of Christianity by missionaries, to the shaping of international law. Even today, one in three drive on the left-hand side of the road, an artifact of the British empire. Yet Britain's idea of its imperial history and the world's experience of the British empire are very different. In Empireworld, award-winning author and journalist Sathnam Sanghera extends hi examination of British imperial legacies beyond Britain. ... Sanghera demonstrates just how deeply British imperialism is baked into our world, and ultimately shows how the largest empire in history still exerts influence in all sorts of silent and unsilent ways."--
Acknowledgments -- Introduction: Spot the colonial inheritance -- The civilized island -- Useful plants -- Phenomenal people exporters -- White saviours -- A rational and intelligible system of law -- The colour line -- Reaping the chaos -- Conclusion: An evolutionary outgrowth -- Bibliography -- Notes -- Index.
Includes bibliographical references (pages 249-307) and index.
Keywords: Imperialism -- History; Impérialisme -- Histoire; Great Britain -- Colonies -- History; Grande-Bretagne -- Colonies -- Histoire